Factors Controlling Magnetism of Reddish Brown Soil Profiles from Calcarenites in Southern Spain: Dust Input or In-situ Pedogenesis? - Liu, Qingsong; Zhang, Chunxia; Torrent, José; Barrón, Vidal; Hu, Pengxiang; Jiang, Zhaoxia; Duan, Zongqi (Frontiers in Earth Science, 2016)
Under aerobic conditions, the A and B horizons of soils are magnetically enhanced due to neoformation of ferrimagnets through pedogenesis. This study systematically investigated soils developed on calcarenites of Neogene age in southern Spain to determine the dominant factors controlling the soil magnetism. Geochemical and clay mineral analyses indicate that aeolian dust significantly contribute to the A and B horizon material of the Spanish soil. Nevertheless, the magnetic enhancement of soils can be simply attributed to the pedogenically produced ferrimagnets in-situ. Therefore, the magnetism of Spanish soils is still linked to paleoclimatic variations regardless of the complexities of aeolian inputs from the Northwestern Africa.